Systemic root signalling in a belowground, volatile-mediated tritrophic interaction - Hiltpold, Ivan; Erb, Matthias; Robert, Christelle Aurélie Maud; Turlings, Ted (My University, 2011)
Plants attacked by leaf herbivores release volatile organic compounds (VOCs) both locally from the wounded site and systemically from non-attacked tissues. These volatiles serve as attractants for predators and parasitoids. This phenomenon is well described for plant leaves, but systemic induction of VOCs in the roots has remained unstudied. We assessed the spatial and temporal activation of the synthesis and release of (E)-β-caryophyllene (EβC) in maize roots upon feeding by larvae of Diabrotica virgifera virgifera, as well as the importance of systemically produced EβC for the attraction of the entomopathogenic nematode Heterorhabditis megidis. The production of EβC was found to be significantly stronger at the site of attack than in non-attacked tissues. A weak, but significant, increase in transcriptional activity of the EβC synthase gene tps23 and a corresponding increase in EβC content were observed in the roots above the feeding site and in adjacent roots, demonstrating for the first time that herbivory triggers systemic production of a volatile within root systems. In belowground olfactometers, the nematodes were significantly more attracted towards local feeding sites than systemically induced roots. The possible advantages and disadvantages of systemic volatile signalling in roots are discussed.
Keywords: Diabrotica virgifera virgifera; Heterorhabditis megidis; belowground tritrophic interaction; entomopathogenic nematode; induced plant defence; systemic root response; volatile emission; Western corn rootworm